Media Usage Patterns of African Higher Education Students: A Ghanaian Perspective - Frank Senyo Loglo (Ubiquity Proceedings, 2023)
The study examined the media usage patterns of 598 university students in Ghana to understand their demands for digital teaching and learning, as well as their patterns of media use for learning, with the goal of informing the media selection process. Overall, the study found that the universities fell short of meeting students' expressed need for digital learning formats. The gap represents both a challenge and an opportunity for the expansion of digital teaching and learning formats in Ghanaian universities. Furthermore, the media usage patterns reveal significant leisure-seeking and recreational uses of media by students, emphasizing the pervasiveness and embeddedness of smartphones in academic contexts. The emphasis on entertainment usage and the prevalent use of media for hedonistic purposes may suggest a deficit in digital skills regarding the use of media for learning. The study found no significant differences in user profiles between traditional and non-traditional students. The implications for instructional design activities and strategies for a mobile-saturated context are discussed.